DNA Barcoding of Red Algae (Rhodophyta) in Ternate Island Sea, North Maluku, Indonesia - Achmad, Muhammad Janib; Akbar, Nebuchadnezzar; Ismail, Firdaut; Samman, Ardan; Subhan, Beginer; E Paembonan, Rustam; Arafat, Dondy (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract Ternate Island is located on the North Maluku Sea. The North Maluku Sea region includes the Wallacea area and the world's coral triangle. One of the organisms commonly found in this sea is red algae. Study aimed to determine the red algae species by phylogenetic tree analysis based on the rbcL gene as a DNA marker. The preserved red algae tissue samples were extracted with the Geneaid GP100 DNA Extraction Kit Plant. The DNA sample was amplified and then visualized by 1% agarose gel electrophoresis. The amplicon products were sequenced and then aligned with the rbcL gene database that was available at the NCBI gene bank. The phylogenetic tree was constructed using the UPGMA method. The results showed that red algae were identified into four species: namely Gibsmithia hawaiiensis (98.65%), C_rbcL sample was identical to Amansieae sp. (91.50%), D_rbcL sample was identical to Peyssonnelia sp. (95.54%), and G_rbcL sample was similar to Portieria hornemanniI (96.15%). Based on phylogenetic tree analysis, Gibsmithia hawaiiensis from North Maluku is closely related to species from Raja Ampat, West Papua, Indonesia, followed by the Philippines species. Special findings were found to carry out phylogenetic reconstructions that can answer inter-species kinship. The general finding is that the markers used can be used for phylogenetic construction. Phylogenetic construction of Peyssonnelia sp. in North Maluku is related to species from South Africa. North Maluku's Portieria hornemannii is closely related to a species from Korea. Highlight Research This study provides initial information about the DNA barcoding of red algae. Important for management purposes and determining the status of red algae in the future. This scientific information also provides an understanding of the relationships among red algae species in the world's oceans. Global warming has changed the temperature of seawater and affected the population of marine organisms.